(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2024)
This document covers the study of a tertiary road located in the village of El Tintal, corresponding to the municipality of Sáchica, Boyacá. In this place, there is an evident deterioration of the sur-face of the road corridor due to lack of maintenance, resources, lack of awareness of the inhabitants who reside there and of the competent authorities. Due to the above, it is necessary to eva-luate the land to execute milling as a viable solution alternative, as a strategy to mitigate the rise of the negative impact present in the area, to satisfy the basic needs of the population in terms of traffic, this because it contributes to the reduction of costs, time and environmental damage.